ANALISA KINERJA KOMISI I (SATU) BIDANG HUKUM PEMERINTAHAN DPRD KABUPATEN KAYONG UTARA DALAM MENUJU PENYELENGGARAAN PELAYANAN PUBLIK YANG BERBASIS TATA PEMERINTAHAN YANG BAIK (Studi Priode 2009-2014) - SYARIF MUHAMMAD DAMIRI, SH A.2021131060, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis addresses the issue of performance analysis Commission I (one) rule of law field Regency North Kayong In the heading of public service that is based on good governance (Study period 2009-2014). From the results of research using normative legal research methods and sociological. One commission in Regency North Kayong is the first commission in charge of law and government. This field perform tasks related to the implementation of laws and legislation, administration, protection of Human rights (HAM), consumer protection, the implementation of regional autonomy, land, licensing, staffing and apparatus, eradication of drugs and alcohol, the eradication of gambling and prostitution, sospol and organizations and the eradication of corruption, collusion and nepotism (KKN) .From the description of duties and authority of legislators of Commission I of the House of Representatives (DPRD) sometimes encounter some weakness that looks like: the low aspirations of members of Commission I DPRD North Kayong in giving opinion and judgment to the District Government of North Kayong in the implementation of the program implemented, the education and training provided to members of Commission I DPRD in the form of technical assistance which was held still a small fraction of participants, so that the performance and quality of work that is owned by members of Commission I DPRD not maximized for example in the preparation APBD, drafting laws, passage of the law proposed Regent and there of members of Commission I of the House who are less responsible for carrying out the tasks assigned to him like; determined to appear in court, proposing or input at meetings. This study used a qualitative research, which illustrates the fact that encountered in the field as it is. The use of this method aims to accurately measure the performance of legislators of Commission I of Governance by using qualitative analysis through pengambaran systematic and gather the facts available. Survey restricted to studies that collected data from a sample that represents the entire populasi.Dari results of research on the performance of members of Commission I DPRD North Kayong then the average respondent to respond less achieved obtained from respondents and informants of the ten indicators of research by the author spread good in the form of the questionnaire and interviews and observations by the author in lapangan.Adapun efforts to improve the performance of Angg ota Regency North Kayong include: providing education and training for members of Commission I DPRD North Kayong, increase the capabilities and potential of themselves and improve expertise and skill.Keywords: analysis, the performance of Commission I, In the operation, public service.ABSTRAKTesis ini membahas masalah analisa kinerja komisi I (satu) bidang hukum pemerintahan DPRD Kabupaten Kayong Utara Dalam menuju penyelenggaraan pelayanan publik yang berbasis tata pemerintahan yang baik (Studi Priode 2009-2014). Dari hasil penelitian menggunakan metode penelitian hukum normatif dan Sosiologis. Salah satu komisi yang ada di DPRD Kabupaten Kayong Utara adalah komisi I yang membidangi hukum dan pemerintahan. Bidang ini melakukan tugas yang berhubungan dengan pelaksanaan hokum dan perundang-undangan, pemerintahan, perlindungan Hak azasi manusia (HAM), perlindungan konsumen, pelaksanaan otonomi daerah, pertanahan, perizinan, kepegawaian dan aparatur, pemberantasan narkoba dan miras, pemberantasan judi dan prostitusi, sospol dan ormas dan pemberantasan korupsi, kolusi dan nepotisme (KKN).Dari uraian tugas dan wewenang anggota DPRD Komisi I Dewan Perwakilan Rakyat Daerah (DPRD) terkadang menemui beberapa kelemahan yang terlihat seperti : rendahnya aspirasi anggota Komisi I DPRD Kabupaten Kayong Utara dalam memberikan pendapat dan pertimbangan kepada Pemerintah Daerah Kabupaten Kayong Utara dalam pelaksanaan program yang dilaksanakan, pendidikan dan Latihan yang diberikan kepada anggota Komisi I DPRD berupa bimbingan teknis yang diselenggarakan masih sebagian kecil pesertanya, sehingga kinerja dan kualitas kerja yang dimiliki oleh anggota Komisi I DPRD belum maksimal misalnya dalam penyusunan anggaran APBD, penyusunan produk hukum, pengesahan Perda yang diajukan Bupati dan masih ada dari anggota Komisi I Dewan yang kurang bertanggung jawab untuk menjalankan tugas yang diberikan kepadanya seperti ; hadir pada sidang yang ditentukan, memberikan usulan atau masukan saat rapat. Penelitian ini mengunakan penelitian kualititatif, yakni menggambarkan kenyataan yang ditemui dilapangan secara apa adanya. Penggunaan metode ini bertujuan untuk mengukur secara cermat kinerja anggota DPRD Komisi I Bidang Pemerintahan dengan menggunakan analisa kualitatif melalui pengambaran sistematis dan menghimpun fakta-fakta yang ada. Survey dibatasi pada penelitian yang datanya dikumpul dari sampel yang mewakili seluruh populasi.Dari hasil penelitian mengenai kinerja anggota Komisi I DPRD Kabupaten Kayong Utara maka rata-rata responden memberikan tanggapan kurang tercapai yang diperoleh dari tanggapan responden maupun informan dari kesepuluh indikator penelitian yang penulis sebarkan baik dalam bentuk hasil kuesioner maupun hasil wawancara dan observasi yang penulis lakukan di lapangan.Adapun upaya-upaya peningkatan kinerja angg ota DPRD Kabupaten Kayong Utara antara lain : memberikan pendidikan dan latihan bagi anggota Komisi I DPRD Kabupaten Kayong Utara,meningkatkan kapabilitas dan Potensi diri dan meningkatkan keahlian dan skill.Kata Kunci : Analisa, kinerja komisi I, Dalam penyelenggaraan,pelayanan publik.